Sikap Toleransi Beragama Siswa Madrasah Aliyah di Kabupaten Kendal Jawa Tengah - Nugroho Eko Atmanto; Umi Muzayanah (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2020)
Madrasah is a formal educational institution that provides education with the uniqueness of the Islamic religion. The condition of the madrasah environment, which is homogeneous and monoculture in terms of religion, impacts student attitudes concerning religious believers' relationship. The interactions that occur in the madrasah environment almost always involve social structures that tend to be homogeneous. This study examines the scholars' tolerance to religious believers' relationship among Madrasah Aliyah students in Kendal Regency. This study uses a quantitative approach with data collection methods through questionnaires. The results showed that most of the students of Madrasah Aliyah in Kendal (74.15%) had an attitude of tolerance among religious believers in the "tolerant" category. Likewise, if seen from the three indicators of tolerance, most students have an attitude of acceptance, respect, and mutual respect between religious believers in the "good" category. However, this also shows that Madrasah Aliyah students have tolerance among religious believers in the "less tolerant" category up to 23.58%. It shows that there is potential for the intolerance of Madrasah Aliyah students in relationships between religious believers. This condition needs to be the concern of madrasah education providers to further develop tolerance education in the madrasah environment.